Anti-Urolithiasis Potential of Phagnaion rupestre: In Vitro Evaluation of Crystal Formation, Aggregation Inhibition, and Stone Dissolution - Magayr, Tajdida; Abdulsalam , Fatima (Libyan Journal of Medical Research, 2025)
Purpose: Urolithiasis, commonly known as kidney stones, is a prevalent condition associated with significant discomfort. Traditional treatments often come with high costs and potential side effects. The use of medicinal plants has gained popularity as a safer, cost-effective alternative. This study aimed to evaluate the anti-urolithiasis potential of Phagnaion rupestre, a plant native to the arid regions of Libya, by assessing its effects on calcium oxalate crystal formation, aggregation, and dissolution. Aim: This study aimed to determine the anti-urolithiasis activity of Phagnaion rupestre through in vitro assays, focusing on crystal formation inhibition, aggregation inhibition, and stone dissolution. Materials and Methods The aqueous extract of Phagnaion rupestre was tested at varying concentrations (250, 500, 750, 1000 μg/mL) for its ability to inhibit calcium oxalate crystal formation, aggregation, and promote the dissolution of pre-formed stones. Synthetic urine and synthetic kidney stones were used for the assays, and the phytochemical profile of the extract was analyzed. Results: The results indicated that Phagnaion rupestre significantly inhibited calcium oxalate crystal formation, with up to 68% inhibition at the highest concentration. Aggregation inhibition was also observed to be dose-dependent, with up to 70% inhibition. Additionally, the extract enhanced the dissolution of pre-formed stones, reaching a dissolution rate of 70%. The phytochemical analysis revealed the presence of bioactive compounds such as phenols, flavonoids, and alkaloids, which are likely contributing to these effects. Conclusion: Phagnaion rupestre demonstrated promising anti-urolithiasis activity by inhibiting calcium oxalate crystal formation, preventing aggregation, and enhancing stone dissolution. These results suggest that Phagnaion rupestre could be a potential natural remedy for the prevention and management of kidney stones, offering a safer alternative to conventional treatments.